The potential significance of microalloying with Nb in enhancing the resistance to hydrogen-induced delayed fracture of 1300-MPa-grade high-strength bolt steel. (May 2022) - Zhang, Chengxiang; Hui, Weijun; Zhao, Xiaoli; Zhang, Yongjian; Zhao, Xiuming
Highlights: Hydrogen-induced delayed fracture (HIDF) of Nb-added bolt steel was evaluated. Significant grain refinement is obtained by the addition of Nb. Hydrogen diffusion coefficient decreases with the addition of Nb. The resistance to HIDF increases with the addition of Nb. The mechanism of adding Nb on enhancing HIDF resistance of bolt steel was explored. Abstract: The present work aims to explore the potential significance of microalloying with Nb in enhancing the resistance to hydrogen-induced delayed fracture (HIDF) of a novel 1300-MPa-grade V-microalloyed high-strength bolt steel 42CrNiMoV using constant load tensile test. The results show that ∼ 82% of the added 0.03 wt% Nb is consumed to form NbC carbides which causes significant grain refinement and thus an overall strengthening of ∼ 60 MPa. The effective hydrogen diffusion coefficient is reduced by ∼ 39% and the corrosion resistance is significantly improved through the Nb addition. The Nb-added steel has enhanced tolerance of diffusible hydrogen content and its resistance to HIDF is enhanced by ∼ 13%. The mechanism of Nb in enhancing the resistance to HIDF was discussed. It is suggested that microalloying with Nb is an effective approach to further improve the HIDF resistance for high-strength bolt steels.